Effectiveness and safety of monoclonal antibodies against amyloid-beta vis-à-vis placebo in mild or moderate Alzheimer's disease - Hao, Ying; Dong, Mingrui; Sun, Yingtong; Duan, Xiaohui; Niu, Wenquan (Frontiers in Neurology, 2023)
Backgrounds and Objectives: Currently, no consensus has been reached upon the therapeutic implications of monoclonal antibodies against amyloid-beta (Aβ) in Alzheimer’s disease. We prepared a meta-analysis by synthesizing data from randomized controlled trials on the effectiveness and safety of monoclonal antibodies against Aβ vis-à-vis placebo in mild or moderate Alzheimer’s disease. Methods: Literature retrieval, article selection and data abstraction were performed by two authors independently. Cognition and function were appraised by MMSE, ADAS-Cog, DAD, and CDR-SB scores. Effect sizes are expressed as standardized mean difference (SMD) with 95% confidence interval (CI). Results: 29 articles involving 108 drug-specific trials and 21,383 participants were eligible for analysis. Of four assessment scales, only CDR-SB was significantly reduced after using monoclonal antibodies against Aβ relative to placebo (SMD: -0.12; 95% CI: -0.2 to -0.03; P=0.008). The Egger’s test indicated a low likelihood of publication bias. At individual levels, Bapineuzumab was associated with a significant increase in MMSE (SMD: 0.588; 95% CI: 0.226 to 0.95) and DAD (SMD: 0.919; 95% CI: 0.105 to 1.943), while a significant decrease in CDR-SB (SMD: -0.15; 95% CI: -0.282 to 0.018). Yet, Bapineuzumab can increase the significant risk of serious adverse events (OR: 1.281; 95% CI: 1.075 to 1.525) and confusion (OR: 1.433; 95% CI: 1.125 to 1.825). Conclusions: Our findings indicate that monoclonal antibodies against Aβ can effectively improve instrumental activities of daily life in mild or moderate Alzheimer’s disease. Particularly, Bapineuzumab can improve cognition and function, as well as activities of daily life, and meanwhile it triggers the occurrence of serious adverse events and confusion.